Relationship between general health with happiness, inferiority feeling and marital conflict in Borujerd city infertile women - Shahverdi, Jamile; Rezaei, Mansour; Ayazi roozbahani, Maryam; Sadeghi, Kheirollah; Bakhtiari, Mitra; Shahverdi, Maryam (Advances in Nursing & Midwifery, 2016)
Abstract Background and aim: Nowadays, infertility and attitudes toward it, cause issues like depression, helplessness and anxiety. The present study aimed to investigate the relationship between general health with happiness, inferiority feeling, and marital conflict in infertile women. Methods and Materials: In this cross-sectional analytical study, 100 infertile women selected by convenience sampling. General Health Questionnaire (GHQ), the oxford happiness scale, inferiority feeling and Kansas Marital Conflict Scale (KMCS) were used as data gathering tools. The Validity of the questionnaires were determined by the content and face validity. The reliability of the questionnaires was determined using the internal consistency method. The calculated Cronbach’s alpha for general health questionnaire, happiness, inferiority feeling and the marital conflicts scale were 88%, 93%, 76%, and 95% respectively. Data was analyzed using SPSS-16 software by a Pearson correlation coefficient and linear regression Results: 100 infertile women 18 - 43 years old with an average age of 29.3 were studied. 55% of women had moderate levels of economic conditions and only 6% of them were referred to a psychologist or psychiatrist. The general health of the women with a minimum of 32 and maximum of 87 and a mean (56/14) was at moderate level. The results showed that there were significant relationship between general health, happiness and inferiority feeling (p <0.01), while there was no significant relationship between marital conflict and general health. Regression analysis showed that happiness and inferiority feeling with respect to the beta coefficient (-0.56, 0.21) can vary significantly predict their general health. Conclusion: General health of infertile women could be affected by the happiness and inferiority feeling. According to the results, it seems that professional assistance from psychologists and clinical psychiatrists is useful in helping infertile patients to cope better with problems caused by infertility. Keywords: Health; Happiness; Inferiority Feeling; Marital Conflict; Infertility